ERRFI1 Inhibits Proliferation and Inflammation of Nucleus Pulposus and Is Negatively Regulated by miR-2355-5p in Intervertebral Disc Degeneration. Issue 15 (1st August 2019) - Guo, Yusong; Tian, Lijun; Liu, Xing; He, Yinxi; Chang, Songtao; Shen, Yong
Abstract : Study Design: In vivo and in vitro studies of the role of miR-2355-5p and its possible targets in intervertebral disc degeneration (IVDD). Objective: To elucidate the regulatory role of miR-2355-5p in IVDD and the underlying mechanisms. Summary of Background Data: IVDD, which is caused by multiple factors, is the main cause of lower back pain with or without extremity pain. However, the underlying cellular mechanisms of IVDD pathogenesis are not well elucidated. Cell hyper-proliferation, inflammation, and epidermal growth factor receptor activation have been implicated in IVDD. Up-regulated miR-2355-5p level was identified to associate with IVDD. ERRFI1 (the product of mitogen-inducible gene 6 [MIG6]) was known to inhibit epidermal growth factor receptor activation. Methods: We monitored the expression of miR-2355-5p and ERRFI1 in IVDD tissues and lipopolysaccharides (LPS)-treated nucleus pulposus (NP) cells. We explored the effects of ERFFI1 on NP cells proliferation and LPS-induced pro-inflammatory cytokines production. We searched the targets of miR-2355-5p and explored the effects of miR-2355-5p on NP cells proliferation and cytokines production. Results: We identified the up-regulation of miR-2355-5p and down-regulation of ERFFI1 in IVDD samples and LPS-treated NP cells. ERFFI1 inhibited NP cells proliferation and LPS-induced pro-inflammatory cytokine production. MiR-2355-5p targeted ERFFI1 and negatively regulated ERFFI1 expression. MiR-2355-5p regulated IVDD by targeting ERFFI1. Conclusion: MiR-2355-5p negatively regulated ERFFI1 and prevented the effects of ERRFI1 on inhibiting NP cells proliferation and inflammation. Level of Evidence: N/A Abstract : We identified the up-regulation of miR-2355-5p and down-regulation of ERFFI1 in IVDD samples and LPS-treated NP cells. ERFFI1 inhibited NP cells proliferation and LPS-induced pro-inflammatory cytokine production. MiR-2355-5p targeted ERFFI1 and negatively regulated ERFFI1 expression. MiR-2355-5p regulated IVDD by targeting ERFFI1.